Design, dynamic modeling, and control of a multistage CO2 compression system. (July 2017) - Modekurti, Srinivasarao; Eslick, John; Omell, Benjamin; Bhattacharyya, Debangsu; Miller, David C.; Zitney, Stephen E.
Abstract: This paper presents a comprehensive model of a post-combustion CO2 compression system that uses a multistage centrifugal compressor train to take the CO2 -rich gas from the regenerator of a CO2 capture system and compress it to the supercritical conditions required for pipeline transport. The compression system model includes inter-stage coolers, flash vessels, glycol tower for water removal, and the CO2 inventory of the associated system. Both inline and integral gear compressors are designed using dimensionless numbers and appropriate design constraints. The steady-state integral gear compressor model is validated against industrial compressor performance data provided by a commercial CO2 compressor manufacturer. Its performance is also compared to the performance of an inline compressor model using a typical feed stream from a post-combustion CO2 capture process. Performance curves using dimensionless exit flow coefficient and isentropic head coefficient are used for simulating off-design performance of the integral gear compressor. To avoid surge during operation, a controller has been designed. Transients of key process variables in response to various disturbances have been studied.